Setting a Colorimetric Assay with MTT for Assessment of Trichomonicidal Activity - Sariego, Idalia; Monzote, Lianet; Rojas, Lazara (Current Clinical Pharmacology, 2014)
Trichomonas vaginalis infection is associated with important problems of public health, including the spreading of other sexual transmitted infections. The existence of clinical resistant isolates metronidazole and tinidazole, the drugs approved for the treatment of trichomoniasis, points to the necessity of continue searching for trichomonicidal substances. Here we optimize a colorimetric assay with MTT to assess trichomonas viability. The absence of ascorbic acid and cysteine in the culture medium was indispensable to perform the assay, as these compounds spontaneously reduce the MTT. Linearity of absorbance was verified versus trichomonas counts. Medium inhibitory concentration of metronidazole was determined using the sigmoidal Emax model, by comparing the absorbance of test cultures with controls. The obtained value was in the range of published data. The test would be used for the evaluation of trichomonicidal activity of chemical compounds and natural products.
Keywords: Trichomonas vaginalis